A Comparative Study of Tools for Anomaly Detection in Software Requirements - Pereira, Fábio Rodrigues; Costa, Heitor Augustus Xavier; Parreira Júnior, Paulo Afonso (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
A software requirement indicates a capability or characteristic that a software system must possess to provide value to its stakeholders. It is essential to ensure that the requirements description is clear and unambiguous to allow for proper understanding and facilitate its evolution. However, since most software requirements are described in natural language, they may contain subjectivity and inconsistencies in their descriptions, which are conventionally referred to as “Software Requirements Anomalies”. Several studies propose tools to aid in the detection of requirements anomalies. However, it can be observed that few of these studies evaluate the effectiveness (recall and precision) of the proposed tools. Therefore, this work presents a comparative study of three anomaly detection tools (RETA, Tactile Check, and Tiger Pro), analyzed based on requirements documents from different domains containing over 85 anomalies. The results show that the Tactile Check tool produced the best results. Despite this, all three analyzed tools demonstrated unsatisfactory levels of coverage and precision, averaging below 66% and 57%, respectively. This indicates that there is room for new contributions in this research area.